2017
DOI: 10.1038/srep45557
|View full text |Cite
|
Sign up to set email alerts
|

Systems approach to characterize the metabolism of liver cancer stem cells expressing CD133

Abstract: Liver cancer stem cells (LCSCs) have attracted attention because they cause therapeutic resistance in hepatocellular carcinoma (HCC). Understanding the metabolism of LCSCs can be a key to developing therapeutic strategy, but metabolic characteristics have not yet been studied. Here, we systematically analyzed and compared the global metabolic phenotype between LCSCs and non-LCSCs using transcriptome and metabolome data. We also reconstructed genome-scale metabolic models (GEMs) for LCSC and non-LCSC to compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…HCC stem cells possess the capacity for self-renewal, differentiation, and responsible for tumor initiation, proliferation and progression. CD44 and CD133 were highly enriched with properties of HCC stem cells [ 36 , 37 ]. Importantly, depletion of B7-H4 led to the decreased CD44 + /CD133 + double positive cell subpopulation, suggesting that the overexpression of B7-H4 in HCC cells might be potentially associated with its stemness properties.…”
Section: Discussionmentioning
confidence: 99%
“…HCC stem cells possess the capacity for self-renewal, differentiation, and responsible for tumor initiation, proliferation and progression. CD44 and CD133 were highly enriched with properties of HCC stem cells [ 36 , 37 ]. Importantly, depletion of B7-H4 led to the decreased CD44 + /CD133 + double positive cell subpopulation, suggesting that the overexpression of B7-H4 in HCC cells might be potentially associated with its stemness properties.…”
Section: Discussionmentioning
confidence: 99%
“…Further, CD133+ cells stemness features are significantly reduced when glycolysis is inhibited [143] . Extensive trascriptome and metabolome analysis of CD133+ HCC cells revealed the key role of MYC in the regulation of glycolytic metabolism in HCC CSCs [144] .…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…When specifically looking at the stem cell compartment, it has been demonstrated that stem-like cells rely on fatty acid oxidation (FAO) for the generation of ATP and NADH [145] [ Figure 2]. Metabolism analysis has revealed that NAD+ concentrations are increased in CD133+ cells, and this is directly correlated with SIRT1-dependent enhanced FAO [144] . In HCC, genome-wide transcriptional profiling and Ingenuity pathway analysis have suggested NANOG to be the connecting point between FAO and stem-like features, because of its simultaneous OXPHOS repression and FAO activation actions [145] .…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…In addition to facilitating the analysis and visualization of existing GEMs, RAVEN particularly aimed to assist semi-automated draft model reconstruction, utilizing existing template GEMs and the KEGG database [10]. Since publication, RAVEN has been used in GEMs reconstruction for a wide variety of organisms, ranging from bacteria [11], archaea [12] to human gut microbiome [13], eukaryotic microalgae [14], parasites [15][16][17], and fungi [18], as well as various human tissues [19,20] and generic mammalians models with complex metabolism [21,22]. As such, the RAVEN toolbox has functioned as one of the two major MATLABbased packages for constraint-based metabolic modelling, together with the COBRA Toolbox [23][24][25].…”
Section: Introductionmentioning
confidence: 99%